Kontribusi KPBS Pangalengan Terhadap Pendapatan Peternak dan Daerah: Analisis Data Sekunder Berbasis Studi Literatur - Refa Husni Hanifah; Fadly Nufradila; Fajar Wirawardana; Urfi Arham; Itto Turyandi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Koperasi Peternak Bandung Selatan (KPBS) Pangalengan is one of Indonesia's largest dairy cooperatives and plays a strategic role in supporting dairy farming and regional economic development in Bandung Regency. This study aims to analyze the contribution of KPBS Pangalengan to regional economic development through a library research approach based on secondary data. The study employed a descriptive qualitative design by systematically reviewing and synthesizing data obtained from scientific journal articles, official government publications, the KPBS annual reports, statistical reports, and relevant regulatory documents. The findings indicate that KPBS contributes to regional economic development through multiple channels, including improving farmers' access to markets and production inputs, strengthening employment opportunities, supporting local economic activities, and generating fiscal benefits through taxes and other region-related economic activities. These findings also demonstrate that the cooperative functions not only as a marketing institution but also as a community-based economic institution that creates multiplier effects for local development. The study contributes to the literature by extending the analysis of dairy cooperatives beyond farmers' welfare to their broader role in regional economic development and local institutional strengthening. The findings provide practical implications for policymakers and cooperative managers in designing policies that reinforce community-based cooperatives as instruments for sustainable regional economic development